Alcohol screening scores and the risk of intensive care unit admission and hospital readmission. Issue 3 (July 2016) - Clark, Brendan J.; Rubinsky, Anna D.; Ho, P. Michael; Au, David H.; Chavez, Laura J.; Moss, Marc; Bradley, Katharine A.
Background : The association between alcohol misuse and the need for intensive care unit admission as well as hospital readmission among those discharged from the hospital following a critical illness is unclear. This study sought to determine whether alcohol misuse was associated with (1) admission to an intensive care unit (ICU) among a cohort of patients receiving outpatient care and (2) hospital readmission among those discharged from the hospital following critical illness. Methods : This was a retrospective cohort study conducted with data from 24 Veterans Affairs (VA) health care facilities between 2004 and 2007. Scores on the Alcohol Use Disorders Identification Test—Consumption (AUDIT-C) questionnaire were used to identify patients with past-year abstinence, lower-risk alcohol use, moderate alcohol misuse, or severe alcohol misuse. The primary outcome was admission to a VA intensive care unit within the year following administration of the AUDIT-C. In an analysis focused on patients discharged from the ICU, the 2 main outcomes were hospital readmission within 1 year and within 30 days. Results : Among 486, 115 veterans receiving outpatient care, the adjusted probability of ICU admission within 1 year was 2.0% (95% confidence interval [CI]: 1.7%–2.3%) for abstinent patients, 1.6% (95% CI: 1.3%–1.8%) for patients with lower-risk alcohol use, 1.8% (1.4%–2.3%) for patients with moderate alcohol misuse, and 2.5% (2.0%–2.9%) for patients with severe alcohol misuse. Among the 9, 030 patients discharged from an ICU, the adjusted probability of hospital readmission within 1 year was 48% (46%–49%) in abstinent patients, 44% (42%–45%) in patients with lower-risk alcohol use, 42% (39%–45%) in patients with moderate alcohol misuse, and 55% (49%–60%) in patients with severe alcohol misuse. Conclusions : Alcohol misuse may represent a modifiable risk factor for a cycle of ICU admission and subsequent hospital readmission.